Hybrid Nb/Al/Ba0.5K0.5Fe2As2 sandwich Josephson junctions. (8th January 2020) - Tian, Wanghao; Lv, Yangyang; Xu, Zuyu; Zhang, Huili; Chen, Shixian; Dong, Sining; Li, Jun; Wang, Yong-Lei; Kölle, Dieter; Kleiner, Reinhold; Wang, Huabing; Wu, Peiheng
Abstract: We fabricated hybrid Josephson junctions between a Ba0.5 K0.5 Fe2 As2 (BKFA) single crystal and the conventional superconductor Nb with normal metal Al as the barrier. An in situ process was used to create clean BKFA/Al/Nb interfaces. Current transport is along the c -axis of BKFA. The current–voltage characteristics are slightly hysteretic at low temperatures. Except for some features indicative of resonant modes the shape of the current–voltage characteristics can be well described by the resistively and capacitvely shunted junction (RCSJ) model, with a product of the Josephson critical current and the normal state resistance of the junction exceeding 180 μ V at low temperatures. The temperature dependence of the Josephson current is linear for temperatures down to 2 K. Under 40 GHz microwave irradiation integer Shapiro steps are observed. The power dependence of the Shapiro step-height is in good agreement with RCSJ simulations. Possible relations of our data with the symmetry of the superconducting order parameter of BKFA are discussed.